Selling sex in unsafe spaces: sex work risk environments in Phnom Penh, Cambodia - Maher Lisa; Mooney-Somers Julie; Phlong Pisith; Couture Marie-Claude; Stein Ellen; Evans Jennifer; Cockroft Melissa; Sansothy Neth; Nemoto Tooro; Page Kimberly (BMC, 2011)
Abstract Background The risk environment framework provides a valuable but under-utilised heuristic for understanding environmental vulnerability to HIV and other sexually transmitted infections among female sex workers. Brothels have been shown to be safer than street-based sex work, with higher rates of consistent condom use and lower HIV prevalence. While entertainment venues are also assumed to be safer than street-based sex work, few studies have examined environmental influences on vulnerability to HIV in this context. Methods As part of the Young Women's Health Study, a prospective observational study of young women (15-29 years) engaged in sex work in Phnom Penh, we conducted in-depth interviews (n = 33) to explore vulnerability to HIV/STI and related harms. Interviews were conducted in Khmer by trained interviewers, transcribed and translated into English and analysed for thematic content. Results The intensification of anti-prostitution and anti-trafficking efforts in Cambodia has increased the number of women working in entertainment venues and on the street. Our results confirm that street-based sex work places women at risk of HIV/STI infection and identify significant environmental risks related to entertainment-based sex work, including limited access to condoms and alcohol-related intoxication. Our data also indicate that exposure to violence and interactions with the police are mediated by the settings in which sex is sold. In particular, transacting sex in environments such as guest houses where there is little or no oversight in the form of peer or managerial support or protection, may increase vulnerability to HIV/STI. Conclusions Entertainment venues may also provide a high risk environment for sex work. Our results indicate that strategies designed to address HIV prevention among brothel-based FSWs in Cambodia have not translated well to street and entertainment-based sex work venues in which increasing numbers of women are working. There is an urgent need for targeted interventions, supported by legal and policy reforms, designed to reduce the environmental risks of sex work in these settings. Future research should seek to investigate sex work venues as risk environments, explore the role of different business models in mediating these environments, and identify and quantify exposure to risk in different occupational settings.